Use of Paper Ash and Lime as a Sustainable Stabilized Materials for Lateritic Soil - Adekunle Isaac Omole; Oyekunle Pius Adegoke; Arafat Ayodeji Adeowu; Musa Odunayo Sabit; Yinka Benjamin Oluwadiya; Ibrahim Ademola Fetuga (The Journal of Engineering and Exact Sciences)
This research investigates the effectiveness of paper ash and lime for stabilizing lateritic soils in road construction applications. We assessed varying concentrations of paper ash and lime (0%, 3%, 6%, and 9%) to evaluate their effectiveness for soil stabilization. Initial analyses, including grain size distribution through wet sieving, specific gravity, moisture content, and Atterberg limits, were conducted to classify the soil. Following this, strength and compaction tests utilized standard proctor compactive energy, a method well-suited for field application. The findings indicated a general reduction in Atterberg limits (liquid limit, plastic limit, and plasticity index), an increase in maximum dry density (MDD), and a decrease in optimum moisture content (OMC) with increased concentrations of paper ash and lime. A thorough analysis of the results, along with a comparison to established standards, demonstrated significant improvements in soil properties. Specifically, the study found that 6% paper ash provided optimal stabilization, while 9% lime was effective as a stabilizing agent. These materials are suitable for use in the construction of subgrades and subbases for roads, aligning with AASHTO standards.